2009
DOI: 10.1542/peds.2008-0211
|View full text |Cite
|
Sign up to set email alerts
|

First-Week Protein and Energy Intakes Are Associated With 18-Month Developmental Outcomes in Extremely Low Birth Weight Infants

Abstract: Increased first-week protein and energy intakes are associated with higher Mental Development Index scores and lower likelihood of length growth restrictions at 18 months in extremely low birth weight infants. Emphasis should be placed on providing more optimal protein and energy during this first week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
346
4
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(381 citation statements)
references
References 44 publications
16
346
4
15
Order By: Relevance
“…25 Although we did not evaluate neurodevelopmental outcome, the findings of more protein received in the first weeks of life has been shown to improve cognitive development scores at 18 months of age. 26 We speculate that cohort 1 received less protein because they were more ill, which is consistent with higher SNAPPE-II scores, need for more respiratory support, more surfactant and greater use of diuretic medication. The SNAPPE-II scores, which reflect the degree of illness at birth, were highest in the infants who subsequently demonstrated postnatal growth failure and who ultimately had the highest incidence of severe BPD.…”
Section: Discussionsupporting
confidence: 56%
“…25 Although we did not evaluate neurodevelopmental outcome, the findings of more protein received in the first weeks of life has been shown to improve cognitive development scores at 18 months of age. 26 We speculate that cohort 1 received less protein because they were more ill, which is consistent with higher SNAPPE-II scores, need for more respiratory support, more surfactant and greater use of diuretic medication. The SNAPPE-II scores, which reflect the degree of illness at birth, were highest in the infants who subsequently demonstrated postnatal growth failure and who ultimately had the highest incidence of severe BPD.…”
Section: Discussionsupporting
confidence: 56%
“…The author pointed out that sometimes conception occurs under conditions of poor nutrition or health, increasing the likelihood that fetal growth and development, and health of the mother during pregnancy will be compromised. Nutrition in the first 1000 days of human life is known to be a critical factor influencing growth and development of a child and the level of contribution that an individual can make to economic development over their lifetime [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In addition, better nutrition may aid in recovery from common neonatal complications, such as chronic lung disease and late sepsis. 10 A recent study by Stephens et al 32 showed that ELBW infants had improved Mental Developmental Index scores at 18 months of age with higher protein intake in first week of life.…”
Section: Discussionmentioning
confidence: 99%